Information and Communication Technology: Students' Health Education in 1st‐ to 6th‐Grade South Korea Elementary Schools. (23rd July 2013) - Lee, Eunjoo; Park, Hyejin; Whyte, James; Jeong, Eunhoe
ABSTRACT: BACKGROUND: The purposes of this study were to (1) identify school nurses' awareness of information and communication technology (ICT) use in students' health education and (2) explore the barriers or reasons for the adoption of ICT in school nursing practice, while (3) presenting strategies to speed ICT diffusion and dissemination into practice. METHODS: For data collection, 209 primary school nurses in K province of Korea were selected and e‐mailed the questionnaires. Collected data were analyzed as frequency, percentages, and chi‐square tests. RESULTS: The major reasons to adopt ICT were increasing school nurses' confidence in providing health education and improving teaching methods using diverse multimedia. The major barriers to utilization of ICT were lack of time for preparation of educational materials, lack of software availability, and lack of computer skills of school nurses and students. Several strategies were suggested to speed the diffusion of ICT into students' health education, such as integrating a health education course into regular curriculum. CONCLUSIONS: It is important to identify barriers and reasons for adoption of ICT in school nursing. In addition, strategies should be emphasized that result in more rapid diffusion of these technologies in school nursing practice.